Study on Chagas disease occurrence in the municipality of Monte Negro, State of Rondônia, Brazilian Amazon - Carvalho, Elaine Oliveira Costa de; Rosa, João Aristeu da [UNESP]; Carvalho, Anderson Antonio de; Chaves, Hialli Cristine Oliveira; Souza, Everton Almeida de; Ostermayer, Alejandro Luquetti; Camargo, Luís Marcelo Aranha de (FapUNIFESP (SciELO), 2011)
Introduction: Studies on Chagas disease deal with the perspective of its occurrence in the Amazon region, which is directly correlated to the population growth and the spread of the bug biotope. The state of Rondônia has an immense source of vectors (Triatomine) and reservoirs of Trypanosoma cruzi. Environmental changes brought forth by the deforestation in the region may cause vector behavior changes and bring these vectors to a closer contact with humans, increasing the probability of vector infection. Methods: This study was carried out to check the occurrence of Chagas disease in the municipality of Monte Negro, Rondônia, Brazil, based on a random sampling of the farms and people wherein blood collection from the population and capturing triatomines were done. The blood samples were submitted to serologic tests to detect antibodies of the IgG class against T. cruzi. The triatomines that were collected had their digestive tract checked for the presence of trypanosomatidae with morphology resembling that of the T. cruzi. Results: The population examined was mostly from other states. From the 322 bugs examined on the microscope, 50% showed parasites with morphology compatible with T. cruzi. From the serology of 344 random samples of human blood, 1.2% was found positive, 6% showed inconclusive results, and 92.8% were negative. Conclusions: Monte Negro shows low prevalence of human infection by T. cruzi and none active vector transmission; however, preventive and surveying measures, which are not performed until now, shall be taken due to the abundance of vectors infected by trypanosomatidae.

Introdução: Estudos anteriores sobre doença de Chagas tratam da perspectiva da ocorrência endêmica da parasitose na região Amazônica, que se correlaciona diretamente com o aumento populacional e a invasão do ecótopo pelos triatomíneos. O Estado de Rondônia possui um imenso manancial de vetores e reservatórios de Trypanosoma cruzi. As modificações ambientais ocasionadas pelo desmatamento na região podem gerar mudanças nos hábitos dos vetores, trazendo-os para um contato mais próximo do homem, aumentando as possibilidades de infecção vetorial. Métodos: Este estudo foi realizado para verificar a ocorrência da doença de Chagas em Monte Negro, Rondônia, equivalente à amostragem aleatória das propriedades rurais e de pessoas residentes no município, onde foram realizadas coletas sanguíneas dos moradores e coleta de triatomíneos. As amostras sanguíneas foram submetidas a testes sorológicos para detecção de anticorpos da classe IgG contra T. cruzi e os triatomíneos coletados foram analisados para verificar a presença de tripanosomatídeos em seu trato digestivo. Resultados: A população estudada, randomicamente selecionada, é em sua maioria advinda de outros estados. Dos 322 barbeiros avaliados microscopicamente, 50% apresentavam flagelados com morfologia compatível com Trypanosoma cruzi. A sorologia das 344 amostras de sangue humano coletadas randomicamente apresentou 1,2% de positividade para T. cruzi, 6,1% de resultados inconclusivos e 92,8% negativos. Conclusões: Monte Negro apresenta baixa prevalência de infecção por T. cruzi em humanos, em torno de 1,2% e sem transmissão vetorial ativa, porém há a necessidade de medidas preventivas de vigilância, não existentes atualmente, devido à abundância do vetor, e a presença de vetores infectados por tripanosomatídeos.
Estudo da ocorrência da doença de Chagas em Monte Negro, Estado de Rondônia, Amazônia Brasileira
Keywords: Chagas disease; Amazon; Trypanosoma cruzi; Triatomines; Doença de Chagas; Amazônia; Trypanosoma cruzi; Triatomíneos